An Penilaian Penyediaan Model Medan Digital untuk Persyaratan Desain Prosedur Penerbangan - Dicky Ananda; Lina Rosmayanti; Mochamad Faisal Muzaki (FTK UNSURYA, 2026)
The provision of Digital Terrain Model (DTM) data plays a critical role in the safe and efficient design of flight procedures within AirNav Indonesia. This study evaluates the workflow and identifies technical gaps in the current DTM data provision process at the Aeronautical Information Cartography Unit. Qualitative research was conducted from January to July 2025, involving semi-structured interviews with six key personnel, direct observation, and document analysis. Results show that all DTM data provision activities depended on a single individual, with no formal standard operating procedures available. This led to recurring delays and data inconsistencies, particularly when the person in charge was absent. To address these issues, a draft standardized technical guideline was developed; however, it has not yet been formally implemented or tested. The presence of this guideline is expected to improve workflow efficiency, ensure data consistency, facilitate effective knowledge transfer, and ultimately contribute to increased operational safety and regulatory compliance in Indonesian aviation